Essential simulation in clinical education - Forrest, Kirsty; McKimm, Judy.; Edgar, Simon (Chichester, West Sussex : John Wiley & Sons, 2013)
This new addition to the popular Essentials series provides a broad, general introduction to the topic of simulation within clinical education. An ideal tool for both teaching and learning, Essential Simulation in Clinical Education provides a theoretical and practical introduction to the subject of simulation, whilst also offering strategies for successful use of simulators within general clinical education and demonstrating best practice throughout. This timely new title provide the latest information on developments in the field, all supported by an evidence-base; content written by a global team of experts; discussion of policy and strategy initiatives to ground simulation within the healthcare context; practical examples of cases, including inter-professional learning. A superb companion for those involved in multi-disciplinary healthcare teaching, or interested in health care education practices, Essential Simulation in Clinical Education is the most comprehensive guide to the field currently available"--Publisher's description.
Essential simulation in clinical education / Judy McKimm and Kirsty Forrest -- Medical simulation : the journey so far / Aidan Byrne -- The evidence what works, why and how? / Doris Ostergaard and Jacob Rosenberg -- Pedagogy in simulation-based training in health care / Peter Dieckmann and Charlotte Ringsted -- Assessment / Thomas Gale and Martin Roberts -- The roles of faculty and simulated patients in simulation / Bryn Baxendale, Frank Coffey, and Andrew Buttery -- Surgical technical skills / Rajesh Aggarwal and Amit Mishra -- The non-technical skills / Nikki Maran, Simon Edgar, and Alistair May -- Teamwork / Jennifer Weller -- Designing effective simulation activities / Joanne Barrott [and others] -- Distributed simulation / Jessica Janice Tang [and others] -- Providing effective simulation activities / Walter J Eppich, Lanty O'Connor, and Mark Adler -- Simulation in practice / edited by Jean Keri -- The future for simulation.
Includes bibliographical references and index.
Print version record.
Keywords: Medical education; Medical education -- Computer simulation; Simulated patients; Education, Medical -- methods; Computer Simulation; Patient Simulation; Computer simulation; Education, Medical -- Methods; Patient simulation; MEDICAL -- Education & Training; Electronic books